Asosiasi Representatif Sebagai Humor dalam Ceramah Ustaz Abdul Somad Dari Persaudaraan Menuju Kebangkitan - Mahmudah, Winda Woro (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This article discusses the use of representative associative speech style in Ustaz Abdul Somad's (UAS) sermons as a means to create humor while delivering religious advice. This linguistic style employs indirect comparisons to clarify meanings and enhance audience comprehension. The study adopts a functional pragmatic analysis method, with data derived from UAS's sermon themed "Dari Persaudaraan Menuju Kebangkitan." The analysis reveals that UAS consistently utilizes this speech style to create a relaxed, enjoyable, and entertaining atmosphere. The pattern involves explaining religious laws, providing examples through comparisons, and emphasizing the core message. This approach not only helps the audience better understand the sermon but also enriches the study of Indonesian language through a pragmastilistic perspective. Moreover, the representative associative speech style can be applied in language and literature education to enhance students’ speaking skills and creativity.